2018
DOI: 10.1039/c7ce01536d
|View full text |Cite
|
Sign up to set email alerts
|

γ-MnS films with 3D microarchitectures: comprehensive study of the synthesis, microstructural, optical and magnetic properties

Abstract: A simple procedure to synthesize 3D microarchitectures of γ-MnS films at low temperature is described in the present work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…This result indicates that, at these concentrations, Mn saturation occurs in the Sb 2 S 3 structure and therefore the formation of MnS also occurred. 50,51 The Raman mode 3 A g , not observed in the Sb 2 S 3 NCs embedded in the SNAB glass matrix, becomes evident at x > 0.00, and its intensity increases with the variation of x from 0.05 to 0.20. This fact can be attributed to the decrease of the structural defects caused by the Sb 3+ -ion vacancy, which is occupied by Mn 2+ ions during the ionic diffusion process at 550 °C, as reported for a Mn-doped nanostructure system.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…This result indicates that, at these concentrations, Mn saturation occurs in the Sb 2 S 3 structure and therefore the formation of MnS also occurred. 50,51 The Raman mode 3 A g , not observed in the Sb 2 S 3 NCs embedded in the SNAB glass matrix, becomes evident at x > 0.00, and its intensity increases with the variation of x from 0.05 to 0.20. This fact can be attributed to the decrease of the structural defects caused by the Sb 3+ -ion vacancy, which is occupied by Mn 2+ ions during the ionic diffusion process at 550 °C, as reported for a Mn-doped nanostructure system.…”
Section: Resultsmentioning
confidence: 98%
“…The band at around 188 cm –1 corresponds to the S–Sb–S bond. It is observed that this band undergoes a blueshift with increasing Mn concentration . This result gives strong indications of the substitution of Mn 2+ ions for Sb 3+ ions in the crystalline structure of Sb 2 S 3 due to the decrease of the atomic mass, thus causing an increase in the frequency of vibration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase and purity of the hybrid product were characterized by the X-ray powder diffraction technique. Figure shows the XRD pattern of the product obtained from the precursors KMnO 4 and thiourea, treated at the temperature of 550 °C for 4 h. Most of the diffraction peaks were matched according to the JCPDS 40-1288 and 40-1289 and could be indexed as the hexagonal phase of γ - MnS. , The face-centered cubic phase of α-MnS (JCPDS 06-0518) also existed in trace amount in the sample . The XRD pattern also indicated the formation of manganese oxide (Mn 3 O 4 ) species during the reaction due to the contact of aerial oxygen, indexed in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…However, the controllable synthesis of the metastable phases of MnS/MnSe is still challenging, because they have low thermal stability and are easy to transform from a metastable phase into a stable phase at high temperature or under high pressure. 12,[17][18][19][20] Most research interest has been focused on the synthesis and electrical properties of MnS nanowires [21][22][23] and polycrystalline films, [24][25][26][27][28] while its non-centrosymmetric properties have been studied rarely. 12,17,18,29 In addition, because of the good substitutional solid solubility between S and Se atoms, the formation of ternary alloys through the S/Se site-substitution provides a platform to tune smart chalcogenide intrinsic physical properties, such as bandgap, 30 which reveals new perspectives in the search for new non-centrosymmetric materials with tunable properties.…”
mentioning
confidence: 99%